1989
DOI: 10.1007/bf01967293
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of rat paw oedema induced byBothrops jararaca venom

Abstract: The mechanism involved in the genesis of the rat paw oedema caused by intraplantar (IPL) injection of Bothrops jararaca venom (BJV) has been investigated. IPL injection of BJV (1 to 30 micrograms/paw) caused a dose- and time-related oedematogenic effect. Oedema was maximal within 1 h after BJV injection, was partially reduced at 6 h and disappeared completely within 24 h. No systemic effect was observed. Previous heating of BJV at 100 degrees C for 3 to 30 min caused a significant inhibition (25%) of its oedem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
1
18

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 33 publications
11
58
1
18
Order By: Relevance
“…Moreover, the fact that L-NAME, but not aminoguanidine, reduced venom-induced edema, strongly suggests that constitutive eNOS, but not iNOS, plays a key role in this phenomenon. Edema induced by Bothrops sp venoms is multifactorial, since a number of infl ammatory mediators are involved [14,43]. NO participates in the edematogenic effect induced by carrageenin in rats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fact that L-NAME, but not aminoguanidine, reduced venom-induced edema, strongly suggests that constitutive eNOS, but not iNOS, plays a key role in this phenomenon. Edema induced by Bothrops sp venoms is multifactorial, since a number of infl ammatory mediators are involved [14,43]. NO participates in the edematogenic effect induced by carrageenin in rats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Such doses have been validated and used in previous pharmacological stud- (8)(9)(10). It has been suggested that the observed poor neutralization is based on the fact that hyperalgesia and edema develop at an extremely rapid rate after venom injection, associated with the release of endogenous mediators involved in these pharmacological effects (15,16,25,26). Thus, by the time antivenom antibodies reach the affected tissues, it is likely that the cascade of inflammatory events associated with hyperalgesia and edema has already started.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that subplantar injection of NhaV can cause a significant paw edema in rats. Envenoming also produced edema and altered vascular permeability in mouse hind paw (42,69). Following these responses, there was an abundant leukocyte infiltration and consequent hemorrhage due to the high doses of Dipyridamole is a potent inhibitor of platelet aggregation.…”
Section: Effects Of Nhav On Rat Paw Edemamentioning
confidence: 99%